An interdisciplinary political ecology of drinking water quality. Exploring socio-ecological inequalities in Lilongwe's water supply network. Issue 84 (August 2017) - Rusca, Maria; Boakye-Ansah, Akosua Sarpong; Loftus, Alex; Ferrero, Giuliana; van der Zaag, Pieter
Abstract: Urban political ecology attempts to unravel and politicize the socio-ecological processes that produce uneven waterscapes. At the core of this analysis are the choreographies of power that influence how much water flows through urban infrastructure as well as where it flows, thereby shaping conditions and quality of access in cities. If these analyses have been prolific in demonstrating uneven distribution of infrastructures and water quantity, the political ecology of water quality remains largely overlooked. In this paper, we argue that there is a clear theoretical and practical need to address questions of quality in relation to water access in the South. We show that conceptual resources for considering differentiated drinking water quality are already present within urban political ecology. We then contend that an interdisciplinary approach, highlighting the interdependencies between politics, power, and physiochemical and microbiological contamination of drinking water, can further our understandings of both uneven distribution of water contamination and the conceptualisation of inequalities in the urban waterscape. We illustrate our argument through the case of water supply in Lilongwe, Malawi. Our political ecology analysis starts from an examination of the physicochemical and microbiological quality of water supplied by the formal water utility across urban spaces in Lilongwe. We then present the topography of water (quality) inequalities in Lilongwe and identify the political processes underlying the production of differentiated water quality within the centralised network. This paper thereby serves as a deepening of urban political ecology as well as a demonstration of how this approach might be taken forward in the analysis of urbanism and water supplies.